Presurgical hyperconnectivity of the ablation volume is associated with seizure-freedom after magnetic resonance-guided laser interstitial thermal therapy. (October 2018) - Ibrahim, George M.; Weil, Alexander G.; Sedighim, Shaina; Schoen, Nathan B.; Mikhail, Mirriam; Sharma, Priya; Guillen, Magno R.; Morgan, Benjamin R.; Wong, Simeon; Cajigas, Iahn; Jermakowicz, Walter J.; Sandoval-Garcia, Carolina; et al.
Abstract: Purpose: Magnetic Resonance-guided Laser Interstitial Thermal Therapy (MRgLITT) is an emerging minimally-invasive alternative to resective surgery for medically-intractable epilepsy. The precise lesioning effect produced by MRgLITT supplies opportunities to glean insights into epileptogenic regions and their interactions with functional brain networks. In this exploratory analysis, we sought to characterize associations between MRgLITT ablation zones and large-scale brain networks that portended seizure outcome using resting-state fMRI. Methods: Presurgical fMRI and intraoperatively volumetric structural imaging were obtained, from which the ablation volume was segmented. The network properties of the ablation volume within the brain's large-scale brain networks were characterized using graph theory and compared between children who were and were not rendered seizure-free. Results: Of the seventeen included children, five achieved seizure freedom following MRgLITT. Greater functional connectivity of the ablation volume to canonical resting-state networks was associated with seizure-freedom (p < 0.05, FDR-corrected). The ablated volume in children who subsequently became seizure-free following MRgLITT had significantly greater strength, and eigenvector centrality within the large-scale brain network. Conclusions: These findings provide novel insights into the interaction between epileptogenic cortex and large-scale brain networks. The association between ablation volume and resting-state networks may supply novel avenues for presurgical planning and patient stratification.